STRATEGI MEMBANGUN KESADARAN MEREK UNTUK MENCIPTAKAN KEPERCAYAAN MASYARAKAT TERHADAP SEKOLAH DI LAJNAH PENDIDIKAN DAN PENGAJARAN (LPP) AL-IRSYAD AL-ISLAMIYYAH PURWOKERTO - Harisatunisa; Meirina Khusnul Azizah; Mughni Zaenal Mukhtar (LP2M IAIN Sultan Amai Gorontalo, 2025)
Brand awareness is the primary foundation for building public trust in educational institutions. Despite being a crucial asset, not all schools have successfully built strong brand awareness like LPP Al-Irsyad Al-Islamiyyah Purwokerto. This study aims to describe LPP Al-Irsyad Al-Islamiyyah Purwokerto strategy in building brand awareness to foster public trust. Using a qualitative case study method through interviews, observation, and documentation, this study shows that LPP Al-Irsyad Al-Islamiyyah Purwokerto applies a structured Hierarchy of Effects model. At the cognitive stage, awareness is built through centralized digital and traditional marketing and strategic networking to instill brand knowledge. The affective stage is achieved by creating differentiation through the international curriculum (IB), engaging alumni, and building a positive narrative to foster liking and preference. Finally, the conative stage is realized through a pre-order system to manage high demand and measurable evaluations to encourage enrollment. As a result, this integrated strategy has proven effective in building brand awareness, leading to the formation of public trust in the school.